Faktor Human, Organization, Technology (HOT-Fit) Dalam Keberhasilan Sistem Informasi Manajemen Rumah Sakit (SIMRS): Studi Literatur (Current Research in Education: Conference Series Journal, 2023)
Evaluation of information systems as an attempt to find out the actual condition of the information system. With the evaluation can be known the condition of the implementation of information systems and can improve the performance of their application. The information system evaluation model that can be used is HOT-Fit which has a measure in human assessment, organization, technology and benefits. On this HOT-Fit model has assessment factors in assessing the success of hospital management information systems. The purpose of this study was to find out on the HOT-Fit model in the success of hospital management information systems. The research method used is the study of literature based on a riview of existing literature. This research uses various sources and references related to the research. Evaluation of information systems as an attempt to find out the actual conditions in information systems. With the evaluation can be known the condition of the implementation of the information system and can improve the performance of the application of the information system. HOT-Fit model as one of the models for the evaluation of this information system can assess the success of the performance of the hospital management information system so that with the evaluation of HOT-Fit the organization's model can manage information system well.